A study of relationship between organisational culture and employee voice at XYZ Sdn Bhd - Lom, Hui Shan (2014)
Getting employee’ opinions and suggestions are very important to the organisation. Organisational culture is one of the factors that have been identified to stimulate and encourage employee voice. Organisational culture is argued to exert a lot of influence in encouraging employee voice in organisations. This study is aimed to examine the relationship between organisational culture and employee voice. A questionnaire was used to collect data about employee voice (i.e. acquiescent voice, defensive voice and ProSocial voice) and organisational culture (i.e. power distance and collectivism). The data were than analyzed using Pearson Correlation and descriptive analysis to answer the study’s research objective. The results of the study show that XYZ SDN BHD practiced a high power distance and collectivism culture. In addition, a high level of acquiescent voice and defensive voice, and moderate level of ProSocial voice was also found. The findings also indicated that employees face difficulty in expressing their points of view as the cultural practices of their organisation inhibit them from expressing themselves. The conclusion drawn from the study is that organisational culture has a relationship with employee voice. It is suggested that superiors need to nurture a more open and transparent communication culture when dealing with their employees which consequently may stimulate and encourage employees to be more daring when voicing their opinions or ideas to the organisation.